THE CORRELATION BETWEEN INTENSITY OF MEMORIZING AL-QUR'AN AND SHORT-TERM MEMORY OF FEMALE STUDENTS AT ISLAMIC BOARDING SCHOOL OF AL-QUR'AN MEMORIZERS - Ashaeryanto; Nur Faizah; Pranita Aritrina (Academic Bright Collaboration, 2026)
This study aims to determine the relationship between the intensity of memorizing the Qur’an and the short-term memory of female students at an Islamic boarding school for Qur’an memorizers. This research used an observational analytic method with a cross-sectional approach. The study was conducted at Al-Askar Islamic Boarding School in Kendari City. A total of 77 respondents were selected using purposive sampling. Data on the intensity of memorizing the Qur’an were obtained from students’ memorization records, while short-term memory was measured using the digit span test. The data were analyzed using the Spearman correlation test. The results showed that 50.6% of respondents had a low intensity of memorizing the Qur’an, while 49.4% had a high intensity. Bivariate analysis indicated a significant relationship between the intensity of memorizing the Qur’an and short-term memory, with a p-value of 0.001 and a correlation coefficient (r) of 0.413. This result indicates a moderate positive correlation, meaning that higher memorization intensity is associated with better short-term memory. The findings suggest that regular Qur’an memorization may contribute to improving cognitive functions, particularly short-term memory. However, this study is limited by its cross-sectional design and the use of a relatively small sample from a single Islamic boarding school. This study provides empirical evidence on the relationship between Qur’an memorization practices and cognitive performance, particularly short-term memory among female students in Islamic boarding schools.